Pengaruh Belanja Pegawai, Belanja Modal, Investasi Pemerintah dan Pembayaran Utang Pemerintah Daerah terhadap Flypaper Effect Di Provinsi/ Kabupaten/ Kota Pemerintah Aceh - Aulia Fikki (Jurnal Telaah dan Riset Akuntansi, 2015)
This study aimed to examine the effect of personnel expenditure, capital expenditure, government investment and local government debt payments either together or partially to flypaper.The population in this experiment is all local governments in Aceh Province, total population of more than 24 local governments consisting of 23 districts / cities and 1 province. This study used secondary data, namely of audited local government financial statements. The analytical method used in this study was the logistic regression analysis. The results of this study indicate that personnel expenditures, capital expenditures, government investment and local government debt payments  together and partially significantly to the  flypaper affect. With variable personnel expenditure, capital expenditure, government investment have negative significant to flypapaer effect and variable local government debt payments have positive significant to flypapae effect.KEYWORDS : personnel expenditure, capital expenditure, government investment, local government debt payments, flypaper effec